2019
DOI: 10.1039/c9fo01630a
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Bifidobacterium longum subspecies infantis strain CCFM687 regulated emotional behavior and the central BDNF pathway in chronic stress-induced depressive mice through reshaping the gut microbiota

Abstract: Probiotics which enhance the biosynthesis of 5-hydroxytryptamine in enterochromaffin cells could alleviate depression symptoms through regulating the CREB-BDNF pathway in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…CREB is up-regulated by chronic antidepressant treatment, and increasing CREB levels in rodent model results in antidepressant-like behaviors. Furthermore, postmortem studies indicate that CREB levels are increased in subjects taking antidepressants at the time of death (Tian et al, 2019). In agreement with that, the red wine extract treatment significantly increased the ratio of pCREB/CREB in the hippocampus and prefrontal cortex.…”
Section: Creb Phosphorylation/ Crebsupporting
confidence: 83%
“…CREB is up-regulated by chronic antidepressant treatment, and increasing CREB levels in rodent model results in antidepressant-like behaviors. Furthermore, postmortem studies indicate that CREB levels are increased in subjects taking antidepressants at the time of death (Tian et al, 2019). In agreement with that, the red wine extract treatment significantly increased the ratio of pCREB/CREB in the hippocampus and prefrontal cortex.…”
Section: Creb Phosphorylation/ Crebsupporting
confidence: 83%
“…With the increasing knowledge of the underlying mechanisms of AD, research has shifted from focusing on Aβ-driven pathologies to studying the role of neuroinflammatory factors during disease progression [ 26 , 27 ]. Probiotics can increase the concentrations of BDNF, growth factors and synaptic markers, and reduce neuroinflammation [ 28 ]. Thus, we next measured the concentrations of 12 different substances in the hippocampus of Aβ 1-42 -treated mice with or without B. breve intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It also increased the level of 5-hydroxytryptamine and brain-derived neurotrophic factor in the brain and decreased depressive behaviors [ 155 ]. Similarly, other studies using the same probiotics, found that treatment of chronically stressed mice with probiotics could restore gut microbiota perturbation, mitigate inflammation, and alleviate depression- and anxiety-like behaviors [ 156 , 157 ].…”
Section: Effect Of Probiotics On the Gut-brain Axis And Neuroinflamentioning
confidence: 85%